Analyzing the Role of Workaholism in Predicting the Human Workforce Effectiveness in Agriculture Banks from Sistan and Baluchistan Province - Dahmardeh, Mohammad Mostafa; Sanadgol, Ahmad; Tavakoli, Hashem; Tajdar, Hamid; Agoshi, Kazem (International Review of Management and Marketing, 2017)
Nowadays, working has become the integral part of the human life. Individuals spend much of their time in the organizations every day. The unlimited pressures imposed and wants asked for by the organizations compel the individuals to be constantly at work. Therefore, they will be more likely to develop workaholism and it can leave positive or negative effects in the related organization. On the other hand, according to the fact that in this era of competition and change, employing committed and effective human force is proposed as a unique competitive advantage for every organization, concepts such as organizational efficiency can be effective on the enhancement of the qualitative and quantitative levels of the employees’ organizational performance and align the employees’ organizational relations in a direction towards stability and comfort. Thus, the present study aims at analyzing the workaholism role in predicting the human workforce efficiency in Agriculture Banks from Sistan and Baluchistan Province. The study adopts a descriptive-correlation approach to the survey of a 419-people population comprised of Sistan and Baluchistan Province’s Agriculture Banks staff. The study takes advantage of a regression correlation coefficient technique to investigate the study subject matter. The results of the study indicated that workaholism and its components influence the human workforce effectiveness. Keywords: workaholism, organizational effectiveness, Agriculture Bank JEL Classifications: C32; O13; O47